2018
DOI: 10.3892/ol.2018.9877
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of SIRT4 inhibits the proliferation of gastric cancer cells through cell cycle arrest

Abstract: The sirtuins (SIRTs) are a family of nicotinamide-adenine dinucleotide (NAD)+-dependent protein deacetylases. SIRT4 is a mitochondrial NAD+-dependent adenosine diphsophate-ribosyltransferase. Recent studies demonstrated that SIRT4 can regulate glutamine metabolism and thus act as a tumor suppressor. However, the association of SIRT4 with gastric cancer remains unknown. The present study investigated the potential role of SIRT4 in the proliferation of human gastric cancer cells. Gastric cancer cell lines (SGC-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…Researchers have shown that SIRT4 overexpression induced arrest of the G1 phase of the cell cycle by inhibiting expression of phosphorylated extracellular signal-regulated kinase (p-ERK), cyclin D and cyclin E ( 75 ). FCM and staining (propidium iodide) revealed that SIRT4 overexpression prominently increased the proportion of cells in the G1 phase and decreased the number of cells in the S phase of the cell cycle.…”
Section: Role Of Sirt4 In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have shown that SIRT4 overexpression induced arrest of the G1 phase of the cell cycle by inhibiting expression of phosphorylated extracellular signal-regulated kinase (p-ERK), cyclin D and cyclin E ( 75 ). FCM and staining (propidium iodide) revealed that SIRT4 overexpression prominently increased the proportion of cells in the G1 phase and decreased the number of cells in the S phase of the cell cycle.…”
Section: Role Of Sirt4 In Cancermentioning
confidence: 99%
“…SIRT4 inhibited expression of cyclin D and cyclin E prominently. In addition, SIRT4 predominantly decreased p-ERK expression, but did not affect ERK expression ( 75 ). It has been reported that ERK controls the G1 phase of the cell cycle by regulating expression of cyclin D ( 76 ).…”
Section: Role Of Sirt4 In Cancermentioning
confidence: 99%
“…There are reports that SIRT4 functions as a tumor suppressor, restraining the growth and proliferation of cells [56,[92][93][94]. SIRT4 can induce G1 cell cycle arrest by inhibiting phosphorylated extracellular signal-regulated kinase, cyclin D and cyclin E in gastric cancer [92]. Moreover, SIRT4 suppresses the malignant progression of non-small cell lung cancer (NSCLC) via ERK-Drp1 pathway-mediated mitochondrial dynamics [57].…”
Section: Tumorigenesismentioning
confidence: 99%
“…This regulatory effect of SIRT4 was modulated by C-terminal binding protein and varied with glucose metabolic levels ( 98 , 99 ). Furthermore, overexpression of SIRT4 blocks cell cycle progression and decreases cancer cell replication by inactivating ERK, p-ERK, cyclin D, and cyclin E in thyroid cancer and gastric cancer cells ( 87 , 94 ).…”
Section: Functions Of Sirt4 In Human Cancermentioning
confidence: 99%